Taxonomic structure of the family Orchidaceae Juss. in flora of Ukraine - V.G. Sobko; M.B. Gaponenko; O.V. Reshetjuk (Інтродукція Рослин, 2004)
The data about quantity of taxons and nototaxons of Ukrainian flora orchids are reviewed. The table for definition species of the genus Dactylorhiza Neck. ex Nevski is given.